New Compressive Sensing Inter Cluster Data Aggregation Based Ileach Protocol For Homogenious Wsns (International Journal of Engineering and Computer Science, 2015)
In the application based WSNs circumstance, vitality and transmission capacity of the sensors are esteemed assets andvital to consume competently. Data collection at the sink by individual sensor nodes results in flooding of the requestswhich results in most extreme energy use. To decrease this issue another data aggregation technique has been used in thispaper which has enhanced the execution of the iLEACH principle by utilizing the LZW compressive sensing basedbetween cluster based data accumulation; additionally called mixture data aggregation strategy, where gathering of nodeswill be carried out on the principle of the available clustering procedures and gathering of cluster heads is likewise done touse the peculiarities to utilizes the cluster head based data aggregation. The proposed technique serves to diminish theenergy utilization issue, furthermore transmission of the aggregated data in proficient way. The proposed technique hasbeen designed and implemented in MATLAB by considering various issues of the WSNs. The comparison among theiLEACH and LEACH has shown the effectiveness of the proposed technique.